Legal validity and soft law - Westerman, Pauline; Hage, J. C.; Kirste, Stephan; Mackor, Anne Ruth (Law and philosophy library, 2018)
This book features essays that investigate the nature of legal validity from the point of view of different traditions and disciplines. Validity is a fascinating and elusive characteristic of law that in itself deserves to be explored, but further investigation is made more acute and necessary by the production, nowadays, of soft law products of regulation, such as declarations, self-regulatory codes, and standardization norms. These types of rules may not exhibit the characteristics of formal law, and may lack full formal validity but yet may have a very real impact on people's lives. The essays focus on the structural properties of hard and soft legal phenomena and the basis of their validity
Literaturangaben
Keywords: Konferenzschrift -- 2015 -- Washington; Konferenzschrift -- 2015 -- Groningen; Rechtsphilosophie; Validität; Soft law